2006
DOI: 10.1073/pnas.0601446103
|View full text |Cite
|
Sign up to set email alerts
|

How photosynthetic reaction centers control oxidation power in chlorophyll pairs P680, P700, and P870

Abstract: At the heart of photosynthetic reaction centers (RCs) are pairs of chlorophyll a (Chla), P700 in photosystem I (PSI) and P680 in photosystem II (PSII) of cyanobacteria, algae, or plants, and a pair of bacteriochlorophyll a (BChla), P870 in purple bacterial RCs (PbRCs). These pairs differ greatly in their redox potentials for one-electron oxidation, E m. For P680, Em is 1,100 -1,200 mV, but for P700 and P870, E m is only 500 mV. Calculations with the linearized Poisson-Boltzmann equation reproduce these measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
111
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(121 citation statements)
references
References 36 publications
10
111
0
Order By: Relevance
“…[31][32][33]. Recently, these effects were found to provide an important contribution to pigment redox potentials in photosynthetic reaction centers (20). Here, we have shown that in the FMO protein, the influence of ␣-helices on the formation of an excitation energy funnel is dominant.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…[31][32][33]. Recently, these effects were found to provide an important contribution to pigment redox potentials in photosynthetic reaction centers (20). Here, we have shown that in the FMO protein, the influence of ␣-helices on the formation of an excitation energy funnel is dominant.…”
Section: Resultsmentioning
confidence: 77%
“…Our simulations take into account all these aspects, allowing us to unravel in detail the various contributions to site energy differences on the basis of a crystal structure. In addition, we consider conformational differences between pigments and the consequences of nonstandard protonation patterns resulting from protein-and environment-induced changes of acid-base equilibria of titratable residues (18)(19)(20). In the classical electrostatic part of the simulations, we calculate the free energy change of the PPC that occurs when the charge density of a pigment in its S 0 state is changed into that of the S 1 state, taking into account the nonequilibrium polarization (21) Author contributions: T.R.…”
mentioning
confidence: 99%
“…Later, Grabolle and Dau (10) analyzed the delayed and prompt Chl fluorescence of PS II membranes in the absence of inhibitor and assessed the E m (P680/P680 ϩ ) value to be ϩ1.25 V, by citing E m (Q A /Q A Ϫ ) to be Ϫ80 mV. Since then, the value of approximately ϩ1.25 V is generally accepted for E m (P680/P680 ϩ ) (1)(2)(3)(4)(5) and is used as a reference in computational chemistry (13)(14)(15)(16).…”
mentioning
confidence: 99%
“…Although the E m (P680/ P680 ϩ ) value is an essential parameter to draw a whole picture of the PS II energetics, its direct measurement has never been attained (10) because water, present as dominant (solvent) molecules in most sample solutions, is oxidized first heavily and tends to mask the subsequent oxidation of the target entity P680 at a higher potential. The E m (P680/P680 ϩ ) value has hence been estimated from the potentials of PS II electron acceptors (10)(11)(12) or assessed by computation (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Eq. (6) Due to the wide range of energies and timescales involved [36][37][38][39][40][41], the graph is robust against large measurement errors ( ± 100 mV in potential, ± an order-of-magnitude in lifetime), so we can be confident of the general trend. It is clear that the high energy states are the most short-lived.…”
Section: The Equivalent Circuit Of the Electron Transport Chain In Phmentioning
confidence: 99%